2019
DOI: 10.1088/2040-8986/ab406b
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical simulation of Gaussian beam interferometric optical tweezers with symmetrical construction

Abstract: Multi-beam optical tweezers can be very effective and suitable for creating optical lattices and dexterous manipulation of the microscopic world. In an earlier work, a symmetrical multi-beam optical tweezers setup was proposed and theoretically investigated. In that study, however, we assumed that the incident beams were plane waves, and a plane wave cannot exist in real situations. The main aim of this paper is to investigate multi-beam optical tweezers under the realistic condition of using the Gaussian beam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The peak value of enhancement factor is 1.5 ~ 3 times for the other peaks. The intensity of the electric field decreases slightly at 600 ~ 650 nm and then peaks, probably due to the interference of incident light with the scattered radiation 30 . Figure 4 b also calculates the Au dimer Raman enhancement factor at excitation wavelength of 635 nm.…”
Section: Resultsmentioning
confidence: 99%
“…The peak value of enhancement factor is 1.5 ~ 3 times for the other peaks. The intensity of the electric field decreases slightly at 600 ~ 650 nm and then peaks, probably due to the interference of incident light with the scattered radiation 30 . Figure 4 b also calculates the Au dimer Raman enhancement factor at excitation wavelength of 635 nm.…”
Section: Resultsmentioning
confidence: 99%
“…The peak value of enhancement factor is 1.5 ~ 3 times for the other peaks. The intensity of the electric eld decreases slightly at 600 nm 650 nm and then peaks, probably due to the interference of incident light with the scattered radiation 24 . This electric eld enhancement factor is a very groundbreaking discovery and provided a reliable data support for SERS development.…”
Section: Resultsmentioning
confidence: 99%
“…In our earlier studies, we suggested a number of different interferometric trapping setups, and their potential applications in optical manipulation were discussed. [19][20][21][22] A dynamic control over periodic interference traps can enhance the capabilities of such periodic patterns and pave the way to some great new applications. One way to do this is to use holographic techniques, 23 but the manipulability of holographic methods is considerably limited by the speed of the beam control.…”
Section: Introductionmentioning
confidence: 99%
“…In our earlier studies, we suggested a number of different interferometric trapping setups, and their potential applications in optical manipulation were discussed. 19–22…”
Section: Introductionmentioning
confidence: 99%